Effect of neuromuscular electrical stimulation in postoperative shoulder rehabilitation: A systematic review and meta-analysis - Edmund Jia Xi Zhang; Gerald Joseph Zeng; Denny Tjiauw Tjoen Lie (Journal of Orthopaedic Reports)
Objectives: Neuromuscular electrical stimulation (NMES) has been posited to augment rehabilitation after shoulder surgery. NMES is able to facilitate muscle contraction and alleviate pain. This systematic review and meta-analysis evaluates the effectiveness of NMES in improving postoperative outcomes for patients undergoing shoulder surgery. Data sources: Medline, Embase. Study selections: A systematic search adhering to PRISMA guidelines was conducted. Articles involving the use of NMES after shoulder surgery were included. Comparative meta-analysis was performed on articles reporting shoulder range of motion (ROM) and visual analogue scale (VAS) scores for NMES. Data synthesis: Three studies consisting of 120 participants were included in the analysis. NMES patients experienced significantly greater pain reduction (MD = −0.60, 95 % CI: −1.17 to −0.04, P = 0.04). However, improvements in shoulder flexion (MD = 5.15° (95 % CI: −2.88 to 13.17°, P = 0.21)), abduction (MD = 3.91° (95 % CI: −5.98 to 12.21°, P = 0.44)), and external rotation (MD = 5.78° (95 % CI: 0.10 to 11.46, P = 0.05)) were not statistically significant. Conclusions: NMES can be a valuable tool in multimodal rehabilitation for postoperative shoulder surgery patients, particularly for pain management. However, its implementation should be considered within the broader context of the patient's overall rehabilitation plan. Further research is needed to standardize NMES protocols and explore its effects on diverse postoperative outcomes.